2018
DOI: 10.4028/www.scientific.net/ssp.282.190
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning of High Aspect Ratio STI Structures for Advanced Logic Devices by Implementation of a Surface Modification Drying Technique

Abstract: The continuous down scaling of the dimensions for the logic devices has imposed to carefully track the pattern collapse issue when cleaning after FIN etch. Showing the limitations of the hot IPA drying technique toward scaled FIN dimensions, a cleaning using a surface modification drying technique has been proposed and successfully implemented. It is also discussed the use of some post treatment solutions to remove the grafted layer used to modify the FIN surface while preserving the integrity of the FIN struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…The drying observation of the HAR structures with aspect ratio of 13.3 using the C1 and C8 confirmed that it is not important to obtain high water repellency, but it is very important to obtain lower surface free energy, as shown in Figure 40 [243]. The alkyl group surface can be easily removed by oxidative or reductive plasma strip by means of N2O or N2/H2 plasmas [244]. Farid et al demonstrated the STI structures with 9 nm CD, 25 nm pitch, and 160 nm fin height [244].…”
Section: Wet Cleaningmentioning
confidence: 85%
See 1 more Smart Citation
“…The drying observation of the HAR structures with aspect ratio of 13.3 using the C1 and C8 confirmed that it is not important to obtain high water repellency, but it is very important to obtain lower surface free energy, as shown in Figure 40 [243]. The alkyl group surface can be easily removed by oxidative or reductive plasma strip by means of N2O or N2/H2 plasmas [244]. Farid et al demonstrated the STI structures with 9 nm CD, 25 nm pitch, and 160 nm fin height [244].…”
Section: Wet Cleaningmentioning
confidence: 85%
“…The alkyl group surface can be easily removed by oxidative or reductive plasma strip by means of N2O or N2/H2 plasmas [244]. Farid et al demonstrated the STI structures with 9 nm CD, 25 nm pitch, and 160 nm fin height [244]. However, silicon oxide powder samples treated with the C1 and C8 showed different results.…”
Section: Wet Cleaningmentioning
confidence: 99%
“…Copper-reflow is a potential gap-fill solution as it eliminates the copper seed overhang formation and creates the perfect bottom-up fill to replace electrochemical plating (ECP). Beyond advanced 7 nm technology, Samsung adopted a "Cu reflow" process improving copper fill ability in smallest design features as part of Back End of Line (BEOL) contacts and metal islands, ensuring manufacturability by aggressive chip scaling [298]. Figure 32 shows the flow diagram for the Cu reflow process on Co liner and the corresponding improvement in electromigration (EM).…”
Section: Metal Materials Interconnectmentioning
confidence: 99%
“…One such problem is the collapse of nanostructures due to capillary interactions during evaporation of cleaning solutions, a process that is exacerbated by increasing miniaturization of semiconductor devices and consequent weakening of nanostructures. The collapse of nanostructures destroys their expected functions, so countermeasures are essential. To solve this problem, new drying techniques to prevent collapse have been developed, such as the addition of an auxiliary substrate, the use of a liquid with a low surface tension to control the wettability of the substrate, , the reduction of capillary forces by electromagnetic-wave irradiation, or the elimination of capillary forces by drying without the involvement of a liquid phase through sublimation or supercriticality. , However, no effective solution has yet been established, and this problem might be one factor that makes it impossible to maintain Moore’s law.…”
Section: Introductionmentioning
confidence: 99%